Stabilizing and improving elastic bioengineered scaffolds mimicking extracellular matrix for use in wound repair and regeneration. (30th December 2021) - Warner, Harleigh; Wagner, William D.
Abstract: Elastic composite scaffolds are used to mimic extracellular matrix in tissue regeneration. They are composed of synthetic elastomers in favor of natural elastin. Many elastomers require thermal polymerization for fiber stabilization. If the scaffold contains protein, additional treatments are required for stabilization. These treatments may modify the structure and function of the scaffold. In the present study a protein‐elastomeric polymer composite of poly (glycerol sebacate), (PGS), silk fibroin, and type I collagen (termed PFC) was used as a model material to investigate a new method to improve stabilization of electrospun fibers. The purpose of this study was to optimize conditions in order to reduce internal flow of an elastomeric prepolymer during fiber fabrication. Co‐electrospun sacrificial poly (ethylene oxide) (PEO) was used to provide scaffold fiber stabilization during fiber formation in order to test different protocols to prevent fiber fusion. Using PEO at a 1:1 ratio with PFC followed by glutaraldehyde treatment, removal of PEO and heat treatment to polymerize PGS resulted in the most stable and consistent fiber morphology. Functionally, scaffolds had increased porosity and improved cell infiltration. The study provides an improved procedure for fabrication of composite electrospun scaffolds requiring stabilization by both chemical and thermal methods. Abstract : The protocol for the hybrid polymeric‐protein scaffold resulted in improved electrospun fiber stability and functionality based on structural analysis, porosity measurements and fibroblast infiltration.